IDENTIFICATION OF GEOTHERMAL PROSPECT AREAS USING REMOTE SENSING TECHNIQUES IN THE MOUNT GALUNGGUNG REGION - Irsyanda, Keisya Adiva; Haryanto, Agus Didit; Hutabarat, Johanes (Faculty of Geological Engineering, Universitas Padjadjaran, 2025)
Geothermal energy sources are economical and have significant potential because Indonesia is located in the Ring of Fire area, which results in numerous tectonic processes that play a role in the emergence of geothermal resource potential. Among Indonesia's many geothermal energy potentials, one is the geothermal resource found in Tasikmalaya Regency, particularly in Mount Galunggung, an area with a geothermal system, as evidenced by geothermal manifestations. This research aims to determine the location of geothermal prospect areas using remote sensing techniques before conducting further research on the reservoir characteristics in a geothermal system in a given area. The study was conducted by analyzing surface temperature, structures in linear features, and field surveys to confirm the location of geothermal manifestations. The research results indicate geothermal prospect areas in the Mount Galunggung region in Sukaratu District, with surface temperature results ranging between 13-29°C.